Contextual History Teaching Module Based on Transformative-Historical Consciousness (Trans-His) to Enhance Historical Awareness Among High School Students - Arif, Suparman; Pratama, Rinaldo Adi; Syaiful M (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
History education in Indonesian secondary schools remains predominantly fact-based, limiting students’ reflective and contextual understanding of historical meaning (verstehen). This study developed and empirically tested a contextual history teaching module grounded in Transformative–Historical Consciousness (Trans-His) learning theory to enhance high school students’ historical awareness. A Research and Development (R&D) design adapted from Borg and Gall was integrated with a quasi-experimental Non-Equivalent Pretest–Posttest Control Group Design. The study was conducted at SMA YP Unila Bandar Lampung and SMA Negeri 2 Metro, Lampung Province, involving 138 Grade XI students (experimental: n = 68; control: n = 70). Five expert validators assessed the module across material, media, and pedagogical dimensions. Quantitative data were analyzed using paired and independent t-tests and the normalized gain (N-Gain) index, with content validity assessed through Aiken’s V and instrument reliability via Cronbach’s alpha (α > 0.80). Expert validation yielded a mean score of 92.35%, classified as highly valid. Effectiveness testing revealed a significant improvement in student comprehension in the experimental group (pretest: 39.74 → posttest: 85.76; N-Gain = 0.83, high category) compared to the control group (40.81 → 71.93; N-Gain = 0.48, medium category). Learning outcomes also improved more substantially in the experimental group (46.94 → 80.07; N-Gain = 0.62) than in the control group (46.81 → 65.21; N-Gain = 0.30). Between-group differences were confirmed as significant at p < 0.001 for both variables. Additionally, 81% of students responded positively to Trans-His instruction across affective dimensions including historical empathy, contextual relevance, and national identity awareness. The Trans-His module is a valid and contextually effective pedagogical innovation that promotes reflective, value-based, and empathy-oriented historical learning. These findings suggest its potential for broader implementation aligned with Indonesia’s Independent Curriculum and multicultural education goals in diverse postcolonial contexts.